2016
DOI: 10.1007/s00436-016-4927-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic, physiological, and biochemical characterization of potentially pathogenic Acanthamoeba isolated from the environment in Cairo, Egypt

Abstract: Acanthamoebae are the most common opportunistic amphizoic protozoa that cause life-threatening granulomatous amoebic encephalitis in immunocompromised individuals and sight-threatening amoebic keratitis (AK) in contact lens wearers. The present work aimed to determine the presence of Acanthamoeba isolates in different environmental sources: water, soil, and dust in Cairo, Egypt and to characterize the pathogenic potential of the isolated Acanthamoeba using physiological and biochemical assays as well as determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…genotype T5. Despite genotype T5 still being categorized as only potentially pathogenic [ 44 ], there have been reports demonstrating its potential pathogenicity through its weak binding capacity to corneal cells in vitro [ 45 ], a cornea infection in the USA [ 46 ], and a case of disseminated cutaneous infection [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…genotype T5. Despite genotype T5 still being categorized as only potentially pathogenic [ 44 ], there have been reports demonstrating its potential pathogenicity through its weak binding capacity to corneal cells in vitro [ 45 ], a cornea infection in the USA [ 46 ], and a case of disseminated cutaneous infection [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted previously in Egypt, reported that 80%, 58.6%, 56.3%, 31.4%, 67.7% and 29.2% of water samples were positive for Acanthamoeba spp. in Beni-Suef governorate, Nile Delta governorates, Giza governorate, Cairo governorate and Faiyum governorate, respectively (Abd El Wahab et al, 2018;Al-Herrawy et al, 2017;Morsy et al, 2016;Tawfeek et al, 2016;Sakran et al, 2017;Gad and Al-Herrawy, 2016). Globally, Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Herrawy et al (2014) identified six Acanthamoeba species from 10 different swimming pools in Cairo; A. polyphaga, A. castellanii, A. rhysodes, A. mauritaniensis, A. royreba and A. triangularis. Tawfeek et al (2016) also detected three isolates; T4, T3, & T5 from environmental sources.…”
Section: Methodsmentioning
confidence: 92%
“…Molecular diagnosis improved AK diagnosis by amplifying Acanthamoeba DNA and detected scanty organisms in clinical cases (Laummaunwai et al, 2012). In the present study, genus-specific primers pair; JDP1 (forward) and JDP2 (reverse) were used for PCR amplification of Acanthamoeba-specific nuclear small subunit ribosomal RNA; 18S rRNA gene segment or the Acanthamoeba specific amplimer-S1 (ASA-S1), which were well accepted (Gatti et al, 2010;El-Sayed et al, 2014;Tawfeek et al, 2016).…”
Section: Methodsmentioning
confidence: 99%